2012
DOI: 10.1590/s0101-20612012005000033
|View full text |Cite
|
Sign up to set email alerts
|

Density and rheological parameters of goat milk

Abstract: The rheological behavior and density of goat milk was studied as a function of solids concentration (10.5 to 50.0%) and temperature (273 to 331 k). Newtonian behavior was observed for values of total solids (TS) between 10.5 and 22.0% and temperatures from 276 to 331 k changing to pseudoplastic behavior without yield stress for TS from 25.0 to 39.4% at the same range of temperature. Goat milk with TS between 44.3 to 50.0% and temperatures of 273 to 296 k showed yield stress in addition to pseudoplastic behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
(8 reference statements)
1
9
0
Order By: Relevance
“…The flow characteristics determine the texture of products, which affects the perception and, thus, the acceptance by consumers. Rheological variables such as yielding stress, consistency index, and apparent viscosity are affected by the composition and the processing conditions of food products (GABAS et al, 2012;ASTOLFI-FILHO et al, 2012MILANI;KOOCHEKI, 2011;REZAEI et al, 2011;CABRAL et al, 2007;GARITTA;SÁNCHEZ, 2004). In a few words, thermophysical and rheological data, and how they behave with temperature variations, are essential to a proper processing of the dulce de leche (DL) in order to avoid losses and to assure a good final quality.…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…The flow characteristics determine the texture of products, which affects the perception and, thus, the acceptance by consumers. Rheological variables such as yielding stress, consistency index, and apparent viscosity are affected by the composition and the processing conditions of food products (GABAS et al, 2012;ASTOLFI-FILHO et al, 2012MILANI;KOOCHEKI, 2011;REZAEI et al, 2011;CABRAL et al, 2007;GARITTA;SÁNCHEZ, 2004). In a few words, thermophysical and rheological data, and how they behave with temperature variations, are essential to a proper processing of the dulce de leche (DL) in order to avoid losses and to assure a good final quality.…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…In contrast, the consistency coefficient ( K ) for both AP and XG hydrocolloids apparently enlarges with increased concentration. Previously, it was reported that as the solid content in goat milk increases, the corresponding value of n decreases [ 55 ]. For purée products made of fruits and vegetables, the solid contents were noticed to have a strong effect on the values of both K and n , and a higher solid content generally yields a larger K and smaller n [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The density of fat that is compacted will be greater than that of fat in the liquid state. Gabas et al (2012), shows that the higher the milk temperature, the lower the milk density.…”
Section: Densitymentioning
confidence: 99%
“…Milk is a food that contains balanced and complete nutrition with a perfect nutritional ratio, so it is needed by humans. The main components of milk dry matters are protein (casein), carbohydrates (lactose), fat, vitamins and minerals (Prasetya, 2012 Research conducted by Gabas et al (2012),…”
Section: Introductionmentioning
confidence: 99%